Matchmaking and Traditionally Arranged Marriages And Domestic Violence In Rural Sindh, Pakistan - Buriro, Ameer Ali; Endut, Noraida (2016)
This paper aims to explore the experience and understandings of men about domestic violence and concepts regarding the different types of marriages performed in the rural Sindh, Pakistan. The participants lived experiences of the male participants’ have been explored to find out the major effects of matchmaking and traditional types of marriage approaches. Apart from that, the men’s perception, social, cultural, and religious beliefs regarding the marriage have been discussed that how does matchmaking and traditionally arranged marriages influence the domestic violence in rural Sindh, Pakistan. Thus, a qualitative study on 12 in-depth interviews with married men from three different age groups – young, middle, and old age of men were undertaken. Data were analyzed using NVIVO software. The major findings indicated that in this type of traditional marriages, men enjoyed the power and superiority over the women, and women are beaten up frequently by husband or by the rest of the male member of the family.